Indirect predictive control techniques for a matrix converter operating at fixed switching frequency - Rivera, Marco (2017)
The following paper presents a novel indirect model predictive control strategy for a direct matrix converter (DMC). The direct matrix converter has a large number of available switching states and therefore the implementation of predictive control techniques require high computational resources. In addition, the simultaneous selection of weighting factors for the control of input and output variables of the converter complicates the system tuning. In this paper, two indirect model predictive control strategies are proposed in order to reduce the computational cost and by doing so avoid the use of weighting factors. The proposal is enhanced with a fixed switching frequency strategy in order to improve the performance of the full system. Results confirm the feasibility of the proposal by demonstrating that it is an alternative to classical predictive control strategies for the direct matrix converter.